Camping and survival - Evans, Jeremy (London : Heinemann, 1992)
Describes the activity of camping, discussing equipment, campsites, cooking, and survival in the wilderness.
Includes index.
Elementary School Library Collection (Bro-Dart).
Horn Book Magazine.
6.8
5-8.
Keywords: Camping -- Juvenile literature; Wilderness survival -- Juvenile literature; Camping; Survival; Wilderness survival; Camping; Survival (After accidents, etc.); Wilderness survival